Persekutuan Hamba Tuhan sebagai Model Pelayanan Sosial Gereja Bethel Indonesia Jemaat Kasih - Witono Witono; Gunawan, Yosua; Prasetya, Giovanita Ellen; Wongdi, Mulia (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service program aims to describe the implementation and impact of “Persekutuan Hamba Tuhan,” a diaconal initiative conducted by GBI Jemaat Kasih Surabaya to support 80 pastors serving in small congregations around the M3 area of Surabaya. The background of the program stems from ongoing socioeconomic challenges affecting church ministers in the post-pandemic period, particularly those serving in churches with limited resources and unstable financial support. Using a descriptive qualitative approach, data were collected through observation of the program activities, documentation of the distribution process, and testimonies from both recipients and church members. The results show three major outcomes. First, the distribution of food packages and basic daily necessities significantly reduced the economic burden of the participating pastors, providing a sense of relief and stability for their households. Second, the program strengthened congregational solidarity, as more than fifty church members actively engaged in fundraising, packaging, and direct service, building a stronger culture of compassion and shared responsibility. Third, the fellowship activities—consisting of worship, preaching, prayer, and personal encouragement—provided emotional and spiritual strengthening that renewed the pastors’ motivation and confidence in their ministry. Overall, this program demonstrates that integrated diaconal service combining material aid, spiritual encouragement, and relational support can offer meaningful impact for vulnerable church ministers. The findings also highlight the potential of this model to be replicated in other church settings as a holistic, community-based ministry approach. It is recommended that future programs expand coverage, incorporate long-term follow-up, and explore empowerment components to enhance sustainable impact.